Warfarin: Influence of Genetic Variations and Their Prevalence in Indian Population - Shalia, Kavita; Raju, Sunila; Chandan, Amit (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Warfarin has been the most trusted but challenging anticoagulant in clinical practice for the last seven decades. The challenge is to manage its dose. A narrow therapeutic index and high inter- and intra-individual variability in drug disposition and response are the factors that shift the pendulum to adverse drug events from one end of fatal hemorrhage to the other i.e. thrombosis. The difficult task for clinical management is to maintain the required international normalized ratio (INR) with warfarin therapy. Factors responsible for this difficult task include both genetic and non-genetic. The predominant genes are those coding for vitamin K epoxide reductase complex (VKORC) subunit 1 (VKORC1; the target of warfarin and the enzyme of warfarin metabolism; cytochrome P450 enzyme 2C9 (CYP2C9). There is general agreement among published retrospective population studies that the combination of VKORC1 and CYP2C9 genotypes, together with gender, age, body mass index or height or weight and concurrent medications, predict approximately 50% of warfarin dose requirement. Thus, genetic testing will be able to predict and help in directing toward the correct dose and reduce the counts of trial and error as well as risks during therapy. Within the Asian population, Indian patients have been reported to require higher warfarin doses than others. Here we also review the prevalence of the genetic variations of VKORC1 and CYP2C9 associated with variable warfarin response in Indian populations from different regions and also depict studies that have aimed at analysing the influence of genotypic variations to the clinical dose of Warfarin in the Indian population.